PENINGKATAN HASIL BELAJAR IPAS MELALUI PROJECT BASED LEARNING PADA MATERI PERUBAHAN WUJUD BENDA KELAS IV DI SEKOLAH DASAR - Rizky Amalia Pujiati; Ahmad Teguh Purnawanto; Wildan Farih Kurniawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
On the subject of changes in the state of matter, the Project Based Learning model is used in this study to maximize the attainment of science. A CAR methodology was employed in the research, which included two cycles with 16 participants: a class teacher and 9 girls and 7 boys from the fourth grade of SDN 3 Tempurejo. Data collection methods include documentation, written exams, observations, and interviews. Quantitative and qualitative data are used in data analysis. This study's innovation is the holistic integration of observation projects, experiments, and posters to improve students' scientific inquiry. According to the study's findings, pre-action data only provided 37.50% of the total learning outcomes. The completeness percentage in cycle I was 62.50%, representing a 30% rise over the pre-action period. In cycle II, the increase in science learning outcomes had a completeness percentage of 87.50% and was 20% higher than in cycle I. This study suggests that the Project Based Learning model can promote the deep learning method in science education in elementary schools and foster more engaging and meaningful learning.